2017
DOI: 10.1108/maj-03-2016-1341
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and risk reporting: Indian evidence

Abstract: Purpose This study aims to measure the extent of voluntary risk disclosure and examine the relationship between corporate governance firm level quality in the form of board characteristics and ownership concentration’s impact on risk disclosure in the annual reports of Indian listed companies. Design/methodology/approach The method adopted in this study is automated content analysis, which is applied to a sample of 100 listed Indian non-financial companies to find out the extent of risk disclosure. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 94 publications
8
144
2
2
Order By: Relevance
“…Furthermore, one the most disclosed content elements is Principal Risks and Their Management, with a score of 0.90 (45 companies out of 50 report this item). Also, this value is higher than the values obtained in previous research [58,59] and can be read in light of the dissatisfaction shown by investors and stakeholders in recent years regarding several corporate scandals and failures, such as those of Enron, Worldcom, and Adelphia, with respect to the general level of risk and risk management disclosure provided by the companies [44,79,80]. Indeed, for investors and stakeholders, a higher level of risk disclosure allows for conducting a better assessment of the risk profile of a company by reducing the equity cost and improving the market efficiency [44,46,81].…”
Section: Compliance Analysismentioning
confidence: 56%
“…Furthermore, one the most disclosed content elements is Principal Risks and Their Management, with a score of 0.90 (45 companies out of 50 report this item). Also, this value is higher than the values obtained in previous research [58,59] and can be read in light of the dissatisfaction shown by investors and stakeholders in recent years regarding several corporate scandals and failures, such as those of Enron, Worldcom, and Adelphia, with respect to the general level of risk and risk management disclosure provided by the companies [44,79,80]. Indeed, for investors and stakeholders, a higher level of risk disclosure allows for conducting a better assessment of the risk profile of a company by reducing the equity cost and improving the market efficiency [44,46,81].…”
Section: Compliance Analysismentioning
confidence: 56%
“…The presence of women directors can increase the frequency and volume in regards to continuous disclosure towards the capital market. This is because women directors encourage more active monitoring and enhance the information environment (Saggar & Singh, 2017). This shows that there is a positive link between the presence of women in a board composition and disclosures.…”
Section: Hypothesis Developmentmentioning
confidence: 90%
“…In response to upturn demand for better risk information disclosure has motivated past studies to further investigate factors who might affect the company risk disclosure (Saggar & Singh, 2017). However, these studies arguably experience some limitations who may open for further research.…”
Section: Fgic2019mentioning
confidence: 99%